Effect of Storage on the Physicochemical Properties of Palm Oil: Short Communication - Abulude, F. O; Ogunkoya, M. O.; Eluyod, O. S. (Biological Sciences - PJSIR, 2005)
The effect of 4-month storage on the physicochemical properties of palm oil stored in earthenware pots, plastic and tin containers is reported. Significant increase was noted in the iodine value (tin, from 48.22 to 57.95; plastic, from 48.22 to 56.68) free fatty acids (tin, from 0.65 to 0.93 %; plastic, from 0.65 to 0.93 %), and peroxide value (tin, from 5 to 8.07 mEq/kg; plastic, from 5 to 7.87 mEq/kg) of the oil during the period of storage. The increase was even more pro- nounced in the earthenware pot in iodine value (from 48.22 to 60.91), free fatty acids (from 0.65 to 0.95%), and peroxide value (from 5 to 8.40 mEq/kg). The sensory quality characteristics were adversely affected during storage in the earthen- ware pots after 4th month of storage. The results suggest that plastic was the best storage container for palm oil.